How does multiple sclerosis affect sexual satisfaction in patients' spouses? - Sedighi, Behnaz; Abedini Parizi, Maryam; Haghdoost, Ali Akbar; Jangipour Afshar, Parya; Shoraka, Hamid Reza; Jafari, Simin (Frontiers in Psychology, 2023)
Background Sexual dysfunction (SD) is a common complaint among multiple sclerosis (MS) patients with a significant impact on the quality of life (QoL) of afflicted couples. The purpose of this study was to determine sexual satisfaction (SS) in the spouses of MS patients and its impact on the QoL. Methods A total of 214 spouses of MS patients were enrolled in this cross-sectional study. They completed the Larson Sexual Satisfaction Questionnaire and SF-8 Health Survey. Results The mean ± SD age of the spouses was 39.8 ± 9.7 years, and the duration of MS was 5 years or less in most of their partners. The mean ± SD score of QoL was 71.0 ± 20.3 (out of 100), and the mean SS score was 89.2 ± 18.6 (out of 125), showing moderate satisfaction. The highest score was among male spouses younger than 40 years old. The SS scores were also lower among female spouses. In the final model, it was found that SD, psychiatric symptoms, cognitive impairment, and the level of disability of patients were independent explanatory factors for the SS of their spouses. Conclusion The findings supported the role of SS in the QoL of spouses of MS patients. Therefore, the attention of physicians to this hidden aspect of the life of MS patients is crucial.